Rural Poverty in Ontario: A Case Study of the Ingersoll Rural Cemetery Potter’s Field - Groat, Cody; Small, Rebecca; Kirk, Emily (Ontario History, 2025)
The unmarked Potter’s Field at the Ingersoll Rural Cemetery was the burial place of nearly 400 people between 1864 and 1976. Many people interred in this section were societally disenfranchised based on their race or their economic circumstances. By utilizing micro-histories, this article presents new and diverse interpretations of the lived experiences of poverty in nineteenth-century Ontario, focusing on death in particular. Narratives relating to the unhoused, victims of infanticide, the formerly enslaved, transient labourers during the Great Depression, and those impacted by the discriminatory Chinese Head Tax are all considered. This article illustrates the ways that previously marginalized histories can be brought into national conversations when considering the nuance and specificity associated with death, burial, and memorialization.